Pengaruh Cadangan Devisa, Jumlah Kendaraan, Dan Subsidi Terhadap Impor Minyak Bumi - Erlangga, Kadek Satrya; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 11, November 2014 (pp.485-548), 2014)
Petroleum as a raw material in the production process of goods and services is a vital factor in supporting production activities in Indonesia. However, many variables that affect the oil change both the value and volume. This study aims to determine the effect of Foreign Exchange Reserves, Total Vehicle and Fuel Subsidy on Petroleum Imports value. The data used in this research is a secondary data sourced from the Central Statistics Agency (BPS), and the Indonesian National Police. Based on the results of the simultaneous study of foreign exchange reserves variable number of vehicles and fuel subsidies have a significant effect on oil imports which described the period 2001-2010. Partially negative impact of foreign exchange reserves / no significant effect on oil imports while the number of vehicles and fuel subsidy partially positive and significant impact on petroleum imports 2001-2010 period. Factors that affect the dominant variable is imported petroleum fuel subsidies.
Keywords: Foreign Exchange Reserves, Number of Vehicles, Subsidies, Fuel Oil, Crude Oil Imports, Influence